The Enhancing students' Cursive Skills using Structural Analytic Sintetic (SAS) Method at Grade 1 Elementary School - Nindi, Faradilla; Azkiya, Hidayati (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The use of the Synthetic Structural Analytical (SAS) method should be able to improve the cursive writing skills of class I students at I SDN 004 Belilas, Kab. Indra Giri Hulu, Riau. However, based on the data, of the 30 class I students, only 11 students got the specified KKM score, namely ≥ 75, while 19 students got a score below the KKM. This means that 63% of students have not completed it so they have to repeat learning the skill of writing cursive letters until they reach the specified KKM score. This research aims to describe the improvement in cursive writing ability using the Synthetic Structural Analytical (SAS) method in class I students at I SDN 004 Belilas, Kab. Indra Giri Hulu, Riau. The theory used is the Synthetic Structural Analytical (SAS) method proposed by Sawitri (2019). This research is classroom action research which pays attention to aspects of planning, implementation of observation and reflection. This research resulted in the conclusion that the use of the SAS method in learning improved the skills of writing cursive letters through the application of the Synthetic Analytical Structural (SAS) method in Class I Students of I SDN 004 Belilas, Kab. Indra Giri Hulu, Riau. Based on the results of research data analysis obtained in cycle I, which was held twice with an average of 61 with a student completion percentage of 24.1% and in cycle II two meetings were held with the average result increasing to 76 with a student completion percentage of 66, 6% has been implemented, it can be concluded that using the Synthetic Structural Analytical (SAS) method can improve the ability to write cursive letters. The results achieved in the first cycle were in the Poor (K) category, and in the second cycle they reached the Good (B) category.